Feminist and ethical aspects of the assisted reproductive technologies (ARTs): Challenges for Social Work - Sewpaul, V (Social Work/Maatskaplike Werk, 2002)
All forms of assisted or new reproductive techniques, such as artificial insemination by husband (AIH), artificial insemination by donor (AID), donor eggs, surrogacy, the gamete intra-fallopian transfer (GIFT), and in vitro fertilisation (IVF), have one thing in common. They all effectively separate reproduction from sexual intercourse. Snowden, Mitchell and Snowden (1983:6) asserted that this simple statement "raises social, moral, and ethical questions which go far beyond the technological and medical considerations that have received most of the publicity to date". Medical technologies do not develop in a vacuum. They reflect complex moral and social issues that scientists are reluctant to debate. These technologies do not merely reflect the social, cultural and political contexts of their development. Their uses in society have quite profound biological, psychological and socio-cultural repercussions that far exceed the complexities of the technologies themselves. This paper addresses some of the debates around the feminist and ethical aspects of the new reproductive technologies.